Hybridizing CNT/PMMA/PVDF towards high-performance piezoelectric nanofibers. (8th June 2018) - Fang, K Y; Fang, F; Wang, S W; Yang, W; Sun, W; Li, J F
Abstract: Piezoelectric nanofibers are of great importance in their potential applications as smart fibers and textiles to bring changes to daily lives. By employing the technique of electrospinning, polyvinylidene fluoride (PVDF) nanofibers modified with polymethyl methacrylate (PMMA) and single-wall carbon nanotubes (CNTs) (referred to as CNT/PMMA/PVDF) are prepared. The electric field induced displacement of the as-prepared nanofibers is characterized by piezoresponse force microscopy. Compared with the pure PVDF nanofibers, the CNT/PMMA/PVDF nanofibers exhibit a great enhancement of about 196% for the electric field induced displacement, while increments of about 104% and 78% are obtained for the PMMA/PVDF and CNT/PVDF nanofibers, respectively. A structural analysis indicates that the hydrogen bonding between the O atom in the carbonyl group of PMMA and the hydrogen atom in the CH2 groups of PVDF, the promotion of the nucleation of crystallites by CNTs, work synergistically to produce the high electroactive response of the CNT/PMMA/PVDF nanofibers. Based on the high-performance nanofibers, a prototype of a flexible nanofiber generator is fabricated, which exhibits a typical electrical output of 3.11 V upon a repeated impact-release loading at a frequency of 50 Hz.